Implementasi Kepemimpinan Kepala Pondok Pesantren dalam Meningkatkan Kualitas Pendidikan Islam di Pondok Pesantren Mu’allimin Klego - Rirmawati Rirmawati; Mohamad Ali (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study discusses the implementation of the leadership of the head of the Islamic boarding school in improving the quality of Islamic education at the Mu'allimin Klego Islamic boarding school. The key to success in educational institutions cannot be separated from the figure of a leader who has a good management pattern. Effective leadership will build good performance in line with the established goals. The purpose of this observation is to describe the implementation of the leadership style of the head of the Mu'allimin Klego Islamic boarding school. This research method is descriptive qualitative to describe a phenomenon objectively according to the reality in the field, without any engineering. This research was conducted at the Mu'allimin Klego Islamic Boarding School, Boyolali. The data collection technique in this study went through several stages, namely observation, interviews, and document studies. Data analysis was carried out in three steps, including data reduction, data presentation, and the conclusion drawing stage. The results of this study show that the head of the Islamic boarding school's efforts to improve the quality of Islamic education within the Mu'allimin Islamic boarding school were successfully implemented using a transformational leadership system. With this transformational leadership, the head of the boarding school was able to realize a solid vision, encourage active participation, develop innovation, increase resource capacity, and create a harmonious environment. With transformational leadership, the head of the boarding school was able to generate clear aspirations and build strong communication with the administrators and was able to mobilize the team to actively participate in efforts to improve the quality of Islamic education.